Perspectives on diagnostic strategies for hyperglycemia in pregnancy – Dealing with the barriers and challenges in South Asia. (November 2018) - Kapur, Anil; Divakar, Hema; Seshiah, Veeraswamy
Abstract: Estimates indicate that south Asia accounts for over two fifths of the global burden of hyperglycemia in pregnancy (HIP) and the ongoing nutritional and epidemiological transition may make the situation worse. Given their higher risk, all women of south Asian decent require to be tested for HIP. With approximately 37 million births annually in the region requires that 37 million women be tested annually; thereby placing a huge burden on the fragile inadequately resourced health systems in the region with poor awareness and lack of trained manpower. Recommendation for testing must therefore be pragmatic, feasible, convenient and cost effective. Diabetes in pregnancy study group India (DIPSI) has proposed a simple testing protocol that is endorsed by the Indian National Guideline on GDM, and by the FIGO guideline on HIP for use in South Asia. This testing protocol has received widespread support in the region. Despite the many challenges it is encouraging to note that in the four large countries in the region – Bangladesh, India, Pakistan and Sri Lanka which account for over 80% of the estimated burden of HIP in south Asia, large scale credible programs have been initiated to address the identified barriers.